2017
DOI: 10.3390/toxins9050152
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Immunochromatographic Strip Test for the Rapid Detection of Alternariol Monomethyl Ether in Fruit

Abstract: A rapid, portable, and semi-quantitative immunochromatographic strip was developed for rapid and visual detection of alternariol monomethyl ether (AME). For this purpose, the anti-AME monoclonal antibody (mAb) was prepared and identified. AME coupled to bovine serum albumin (BSA) via methyl 4-bromobutanoate was prepared as immunogen. The recoveries of AME in spiked cherry and orange fruits determined by competitive ELISA were 86.1% and 80.7%, respectively. A colloidal gold nanoparticle (CGN) and CGNs-mAb conju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The first antibodies and immunoassays for AOH were reported in 2011 [10,11]. Since then, a few immunoassays have been described using either polyclonal or monoclonal antibodies specific to AOH [12,13], and only one study has been published using an antibody specific to AME [14]. Additionally, Wang et al have reported a generic antibody for both mycotoxins [15].…”
Section: Introductionmentioning
confidence: 99%
“…The first antibodies and immunoassays for AOH were reported in 2011 [10,11]. Since then, a few immunoassays have been described using either polyclonal or monoclonal antibodies specific to AOH [12,13], and only one study has been published using an antibody specific to AME [14]. Additionally, Wang et al have reported a generic antibody for both mycotoxins [15].…”
Section: Introductionmentioning
confidence: 99%
“…The following reagents were used: PBS; boric acid buffer solution (0.2 mol/L); resuspension solution, gold label pad treatment solution, sample pad treatment solution, sample buffer [23].…”
Section: Reagents and Solutionsmentioning
confidence: 99%
“…However, in beverages, these methods have largely been disseminated for alcoholic drink (e.g., wine and grape must [211]), milk [212,213] and cereal analysis [214]. Recent reports have described the use of these techniques to assess Alternaria toxins in fruit [215] and fruit juice [216].…”
Section: Non-chromatographic Multiple Mycotoxin Analysismentioning
confidence: 99%